Floral Induction of Longan (Dimocarpus longan) by Potassium Chlorate: Application, Mechanism, and Future Perspectives - Huang, Shilian; Han, Dongmei; Wang, Jing; Guo, Dongliang; Li, Jianguang (Frontiers in Plant Science, 2021)
Longan (Dimocarpus longan L.) is one of the most important tropical and subtropical fruits in the world. Longan fruit has high nutritional and medical value, and is regarded as a treasure among fruits. Since it was first reported that potassium chlorate (KClO3) could be successfully applied to promote flowering in longan, this compound has been widely used in the production of on-season and off-season longan fruits. KClO3 has thus played a great role in promoting the development of the longan industry. In this review, we summarize the application methods, influencing factors, and physiological and molecular mechanisms associated with KClO3-mediated induction of longan flowering. It can be deduced that leaves may play a crucial role in the transport of and response to KClO3. Leaves supply carbon and nitrogen nutrition, and hormone and signaling molecules needed for the differentiation of apical buds. Moreover, cytokinins may be crucial for KClO3-mediated induction of longan flowering. More effort should be focused on studying the molecular mechanisms underlying this process. This will not only help us to better understand floral induction by KClO3 in longan but also enrich our understanding of flowering regulation mechanisms in woody plants.